Fortune at the Bottom of the Pyramid, Video Case Studies, the - Prahalad, C. K. (Pearson, 2010)
Video Case Studies: Produced by C.K. Prahalad's students, these videos illustrate the case studies presented in the book. The Market Exists at the Bottom of the Pyramid Casas Bahia Produced by Andrew Wilson and Sami Foguel In fifty years, Casas Bahia has grown from one man selling blankets and bed linens door-to-door to the largest retail chain in Brazil, offering electronics, appliances, and furniture. With its emphasis on serving the poor customer, its low prices, and credit determined by payment history rather than formal income (70 percent of Casas Bahia customers have no formal or consistent income), Casas Bahia grosses over US$1 billion, and has invoked deep loyalty in its customers. CEMEX Produced by Ajit Sharma, Sharmilee Mohan, and Sidharth Singh The third largest cement manufacturer in the world, Cemex decided it needed to move from selling materials to selling solutions. With low fixed prices, materials on credit, pre-costed housing designs, and even supervised construction services for Mexicans working abroad, Cemex makes housing affordable and possible for the poor in Mexico. Known Problems, Known Solutions Salt-Hindustan Lever Limited Produced by Anuja Rajendra and Tej Shah In India, Iodine Deficiency Disorder hinders the growth and intellectual development of 70 million people, with twenty percent of the population at risk. Yet up to fifty percent of the iodine in iodized salt can be lost during storage, transportation, and Indian cooking. Using world-class technology, Hindustan Lever Limited has developed a more stable iodine for salt that is effective in preventing IDD and affordable; using village-based entrepreneurs to sell products in remote areas, HLL is ensuring its availability, as well as providing jobs, income, and self-respect for the poor. Soap-Hindustan Lever Limited Produced by Mindy Murch and Kate Reeder Around the world, 2.2 million people die from diarrheal disease every year. Children are especially at risk-one child dies every 30 seconds. India alone contributes thirty percent of the world's diarrheal deaths. By teaching and demonstrating the benefits of handwashing through both UN and branded programs that reach into the villages, Hindustan Lever Limited is reducing infectious disease and improving soap sales. Aravind Eye Hospital Produced with the permission of Aravind Eye Hospital From an eleven-bed clinic, Aravind Eye Hospital has grown to the largest eye care facility in the world. Their innovations in operati ...